Differential scanning calorimetric analysis for determination of some animal fats as adulterants in palm olein - Marikkar, J.M.N.; Ghazali, H.M.; Che Man, Y.B.; Lai, O.M. (Blackwell Publishing, 2003)
A study was conducted to assess the use of differential scanning calorimetry (DSC) for monitoring the presence of common animal fats such as genuine lard (GLD), chicken fat (CF) and beef tallow (BT) as adulterants in palm olein. Pure palm olein samples spiked separately with GLD, CF and BT in various levels (1 to 20%) were analyzed using DSC to obtain the cooling profiles. High performance liquid chromatographic (HPLC) analyses were also performed to obtain compositional changes in triacylglycerols (TAG) of these samples. Qualitative differences in the cooling-thermograms of adulterated samples are proposed as a basis for identification of adulteration peaks and differentiating the unadulterated sample of palm olein from those adulterated with the above mentioned animal fats. As the adulteration increased from 3 to 20%, the peaks corresponding to GLD and CF were found to appear in the low-temperature region below -42.75C whereas that corresponding to BT adulteration appeared in the high-temperature region above 8.5C. Despite their close proximity in position, GLD and CF adulteration peaks were shown to be distinguishable by making use of the subtractive procedures facilitated by the DSC computer software.